Le regard critique en situation d’immersion - Nicolas Horvat (Socio-anthropologie, 2013)
The ethnographic approach generally raises a number of issues concerning the relationship of the researcher with his field. Concerning the views and judgments the researcher has on the object under examination and the specificity of the area of research, this approach can prove to be a difficult experience. Based on an observation conducted in a CCTV control room, this article objective is to contribute to a reflection on such “embedded” experiences which deeply questioned the positioning of the researcher. Following an examination about the reasons that encouraged the adoption of ethnographic approach, strategic constraints related to environmental characteristics and uncertainty regarding the immersion into the universe under investigation the objectives will be to consider the possible conditions for analysis which are resolutely critical and as near as possible to the reality of the field.